2022
DOI: 10.3389/fenrg.2022.825994
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Energy Generation Evaluations of Large-Scale Photovoltaic Plants Equipped With Panel-Level DC Optimizers

Abstract: The distributed maximum power point tracking (DMPPT) technology, based on a DC optimizer (DCO, a DC/DC micro-converter) for each single photovoltaic (PV) panel, is one of the most popular solutions to mitigating the waste of solar energy when suffering mismatch conditions. However, the trade-off between the additional costs of deploying the panel-level power electronic equipment and the improved generation benefits of a large-scale PV plant (LPP) remains to be further studied. This study presents a static mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…While MLPE were designed to recover the power loss from panel mismatch, the string or centralized inverter was not designed to recover the power loss from panel mismatch, so the comparison between PV systems using MPLE and PV systems using a string or centralized inverter under PSC seems unfair. Finally, Figure 8 summarizes the difference between our study and other existing studies [12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…While MLPE were designed to recover the power loss from panel mismatch, the string or centralized inverter was not designed to recover the power loss from panel mismatch, so the comparison between PV systems using MPLE and PV systems using a string or centralized inverter under PSC seems unfair. Finally, Figure 8 summarizes the difference between our study and other existing studies [12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 84%
“…However, more studies are required to verify the ability of improving the energy harvested from PV systems under PSC. While other studies in the literature [12][13][14][15][16][17][18][19] have shown the advantage of using MLPE (microinverter or DC optimizer) over the string or centralized inverter under partial shading conditions and in nonshading conditions, the energy performance of a string or centralized inverter is shown to outperform MLPE (especially when the string or centralized inverter is integrated with MPPT (maximum power point tracking)), our study revealed for the first time, (while, to the extent of our knowledge, the past literature did not), that MLPE did not effectively improve the energy harvested from PVs under PSC compared with that in NSC. While MLPE were designed to recover the power loss from panel mismatch, the string or centralized inverter was not designed to recover the power loss from panel mismatch, so the comparison between PV systems using MPLE and PV systems using a string or centralized inverter under PSC seems unfair.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation